2021
DOI: 10.1007/s00426-021-01526-1
|View full text |Cite
|
Sign up to set email alerts
|

Group membership does not modulate automatic imitation

Abstract: Individuals have the automatic tendency to imitate each other. A key prediction of different theories explaining automatic imitation is that individuals imitate in-group members more strongly than out-group members. However, the empirical basis for this prediction is rather inconclusive. Only a few experiments have investigated the influence of group membership using classic automatic imitation paradigms and these experiments led to mixed results. To put the group membership prediction to a critical test, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
2
14
1
Order By: Relevance
“…Taken together, social modulation theories of imitation (e.g., Chartrand & Dalton, 2009; Wang & Hamilton, 2012) suggest that group membership should affect the way individuals imitate in- versus out-group members. However, the empirical basis for this effect is rather unclear, as recent studies were not able to find an influence of group membership on automatic imitation (De Souter et al, 2021; Genschow, Westfal et al, 2021; Weller et al, 2020). A disadvantage of previous research investigating the link between group membership and imitation is that researchers confounded movement-based with goal-based imitation.…”
Section: Present Researchmentioning
confidence: 93%
See 2 more Smart Citations
“…Taken together, social modulation theories of imitation (e.g., Chartrand & Dalton, 2009; Wang & Hamilton, 2012) suggest that group membership should affect the way individuals imitate in- versus out-group members. However, the empirical basis for this effect is rather unclear, as recent studies were not able to find an influence of group membership on automatic imitation (De Souter et al, 2021; Genschow, Westfal et al, 2021; Weller et al, 2020). A disadvantage of previous research investigating the link between group membership and imitation is that researchers confounded movement-based with goal-based imitation.…”
Section: Present Researchmentioning
confidence: 93%
“…However, the empirical basis for the idea that imitative behaviour is moderated by social group membership is less clear than previously assumed. Although some researchers find that in-group members are more strongly imitated in automatic imitation paradigms than out-group members (Genschow & Schindler, 2016; Gleibs et al, 2016), others were not able to replicate this finding (De Souter et al, 2021; Genschow, Westfal et al, 2021; Rauchbauer et al, 2015, 2016; Weller et al, 2020). For example, De Souter et al (2021) did not find a difference in automatic imitation between the imitation of in- and out-group members in a multi-agent paradigm.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…That is, one hand had a pale skin tone and one hand had a dark skin tone (counterbalanced; Figure 1). Previous research has shown that skin tone as such does not influence automatic imitation, not even when tested in large samples (N = 297 and N = 737; Genschow et al, 2022). After the experiment, participants were asked whether they thought the hands belonged to two different persons or to the same person.…”
Section: Task and Proceduresmentioning
confidence: 99%
“…Social modulations of observing a motion sequence onscreen depicting an irrelevant yet (in-)compatible action are documented for the automatic imitation task (Brass et al, 2001;Butler et al, 2016;Cracco, Genschow, et al, 2018b; for an overview, see Cracco et al, 2018a, b). For instance, individuals imitate others less strongly when they observe actions from a third-person perspective compared with a first-person perspective (Bortoletto et al, 2013;Genschow et al, 2013;Lamm et al, 2007;Vogt et al, 2003) or when they face out-group compared with in-group members (Genschow & Schindler, 2016; but see Genschow, Westfal, et al, 2021b, for a failed replication of this finding). Similarly, joint Simon effects emerge for situations in which participants believe to observe the action of a human interaction partner seated in an adjacent cubicle (Tsai et al, 2008).…”
mentioning
confidence: 99%